감각의 블록으로서 버지니아 울프의 『파도』: 들뢰즈의 미학을 중심으로 - 김금주(Kumjoo Kim) (영미연구, 2024)
본 논문은 버지니아 울프의 『파도』를 들뢰즈의 미학을 통해 연구한다. 들뢰즈에 의하면 지각과 정동의 복합체인 감각의 블록을 통해 구현된 예술 작품은 미리 전제된 경험적 표상으로 표현될 수 없는 감각의 발생으로 이끄는 실험이자 사건이다. 따라서 예술작품은 재인되어 지각상태로 굳어지지 않은 힘들과, 감각을 발생시키는 힘이 신체에 가하는 작용을 포착한다. 이렇게 감각되지 않은 힘을 포착하는 예술은 재인된 지각상태와 정동상태, 그리고 의견으로 이루어진 삼중의 조직을 해체하고, 지각작용과 정동작용의 문턱 위나 아래에 있는 생성의 양상을 구현한다. 들뢰즈는 지각과 정동이 구현된 예술이 감금된 삶을 해방시키거나, 불확실한 투쟁 속으로 유인하는 것에 대한 문제를 다룬다고 주장했다. 들뢰즈는 이처럼 감금된 삶으로부터 해방되기의 문제를 탐색한 예술가로 버지니아 울프를 주목했다. 울프는 글쓰기에서 일상적인 지각작용을 넘어 생성의 양상을 포착할 것을 주장하며 무수한 인상들이 원자들의 소나기로 쏟아지는 순간 전체를 포착할 것을 강조했다. 울프는 바로 이러한 순간의 인상들, 들뢰즈가 말한 감각되지 않았던 힘들을 포착하는 작업을 『파도』에서 보여준다. 『파도』에서 울프는 감각되지 않은 힘들을 포착할 뿐 아니라 그러한 힘들이 신체에 미치는 영향을 통해 알려지지 않은 새로운 정동들을 창안하여 그것들을 인물들의 생성으로 발현시킨다. 그리하여 울프는 주인공들의 생성 혹은 되기를 구현하면서 예술가로서 의견의 상투적 표현에 맞서 억압된 삶으로부터의 해방과 새로운 삶의 가능성을 모색한다. 울프는 이렇게 자신만의 고유한 감각의 언어로 쓰인 『파도』를 통해 우리를 새롭게 생성되도록 하며 우리에게 유기체적 질서를 추구하는 감금된 삶에서 벗어날 것을 촉구한다. This paper studies Virginia Woolf's The Waves through Deleuze's aesthetics. According to Deleuze, the work of art as a bloc of sensations or a compound of percepts and affects is an experiment or an event that leads to the occurrence of sensations, which cannot be expressed with a predetermined empirical representation. Such art captures the forces that are the generative elements of sensations and not hardened into perceptions by recognition, and the action of forces upon the body. Thus art that captures insensible forces undoes the triple organization of perceptions, affections, and opinions, and embodies the aspects of becomings that are below or above the threshold of perception and affection. Deleuze argues that art deals with a question of freeing life wherever it is imprisoned, or of tempting it into an uncertain combat. Virginia Woolf is an artist who explored the problem of being freed from such a life of confinement. Woolf emphasized capturing the entire moment when a myriad of impressions pour into a shower of innumerable atoms, insisting on capturing the aspects of becoming beyond everyday perceptions in writing. Woolf shows the work of capturing the impressions of these moments, the insensible forces in the Waves. And Woolf not only captures the imperceptible forces, but also invents unknown or unrecognized affects and brings them to light as the becomings of his characters in the Waves. Thus, Woolf seeks freeing from the imprisoned life and new possibilities in life against the clichés of opinion by embodying the becomings of the protagonists. And she urges us to lead to new becomings and escape from the imprisoned life through The Waves written in her own style, the language of sensations. KCI Citation Count: 0